2015
DOI: 10.1016/j.corsci.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sealing on the morphology of anodized aluminum oxide

Abstract: Ultra-small angle x-ray scattering (USAXS), small-angle neutron scattering (SANS), x-ray reflectometry (XRR) and neutron reflectometry (NR) were used to probe structure evolution induced by sealing of anodized aluminum. While cold nickel acetate sealing and hot-water sealing decrease pore size, these methods do not alter the cylindrical porous framework of the anodic aluminum oxide layer. Hot nickel acetate both fills the pores and deposits on the air surface (air-oxide interface), leading to low porosity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 30 publications
4
47
0
2
Order By: Relevance
“…When immersing the sample in NaCl solution, the electrolyte can easily pass through the porous layer, thus only the information of barrier layers can be obtained during impedance spectroscopy . In the case of the sealed anodized sample, the nano‐pores are almost filled due to the volume expansion of the alumina or the formation of products in the sealing process . Therefore, the structure of the porous layer changes, such as a decrease in the radius of the pores and an increase in the thickness of the pore walls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When immersing the sample in NaCl solution, the electrolyte can easily pass through the porous layer, thus only the information of barrier layers can be obtained during impedance spectroscopy . In the case of the sealed anodized sample, the nano‐pores are almost filled due to the volume expansion of the alumina or the formation of products in the sealing process . Therefore, the structure of the porous layer changes, such as a decrease in the radius of the pores and an increase in the thickness of the pore walls.…”
Section: Resultsmentioning
confidence: 99%
“…Cr(VI) used for dichromate sealing is limited by the high toxicity and nickel salts are not only expensive but also contain toxic. Thus, they cannot be used in the food industry . Up to date, some green sealing methods have been proposed, including sol‐gel sealing, organic acid sealing, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors found that the modification of conditions for the reflectivity measurements (e.g., limited currents) led to a different structure to that observed with the other techniques where the current was unlimited. Whereas the SAXS and SANS results showed varying penetration of the different sealing agents, the AA films studied by NR appeared to have their pores capped during the anodisation process [89]. Their work demonstrated the high desirability of combining a range of complementary techniques to study a corrosion system.…”
Section: Aluminiummentioning
confidence: 99%
“…For instance, nanotitania can be used to seal aluminum oxide for corrosion resistance and UV-protection by virtue of the commonly-known physiochemical stability and UVshielding performance of the nanotitania [42,43]. However, it remains a great challenge to use nanotitania as a hole sealing material for AAO film [23][24][25][26][27][28][29][30][31][32][33][34] This study aims to grow a layer of nanotitania film for the purpose of sealing the holes of the AAO film on the aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotitania has been regarded as the most promising semiconductor catalyst and environmentally friendly photocatalytic material, owing to its impressive photocatalysis, hydrophilicity, high electron-hole counter potential, and good physiochemical stability, low cost, non-toxicity and ready availability [19][20][21][22][23][24]. As a consequence, nanotitania has been extensively explored across various scientific disciplines [21,22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%